Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4081/monaldi.2020.1255
|View full text |Cite
|
Sign up to set email alerts
|

Leadless pacing in the elderly: never too old for something new

Abstract: Rates of cardiac pacemaker implantation rise with age, and, meanwhile, elderly patient may be at great risk of complications, as pneumothorax, lead perforation, or pocket dehiscence. The use of leadless pacemaker could overcome peri- and post-procedural complications related to the presence of transvenous leads and pocket. The study aims to investigate feasibility and outcomes of Micra Transcatheter Pacing System (M-TPS) implantation in elderly, which represents a challenge for conventional cardiac pacing. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…The success rate of Micra TPS implantation in the total population was 98.6% which is in line with data from the IDE (99.2%) as well as the post-market registry (PAR) (99.1%) [8]. Furthermore, it is comparable to observational data from other registries focusing on the elderly population which also reported successful implantation rates of >98% [10][11][12][13]. However, previous studies on Micra TPS in octogenarians have either included a lower number of patients or focused on the comparison of leadless versus conventional transvenous pacemaker implantation in octogenarians, while our study included a higher number of patients in the octogenarian group and focused on the comparison of clinical outcome of Micra TPS implantation in non-octogenarians versus octogenarians.…”
Section: General Comparison Between Octogenarians and Non-octogenarianssupporting
confidence: 87%
See 1 more Smart Citation
“…The success rate of Micra TPS implantation in the total population was 98.6% which is in line with data from the IDE (99.2%) as well as the post-market registry (PAR) (99.1%) [8]. Furthermore, it is comparable to observational data from other registries focusing on the elderly population which also reported successful implantation rates of >98% [10][11][12][13]. However, previous studies on Micra TPS in octogenarians have either included a lower number of patients or focused on the comparison of leadless versus conventional transvenous pacemaker implantation in octogenarians, while our study included a higher number of patients in the octogenarian group and focused on the comparison of clinical outcome of Micra TPS implantation in non-octogenarians versus octogenarians.…”
Section: General Comparison Between Octogenarians and Non-octogenarianssupporting
confidence: 87%
“…In addition to advanced age being a risk factor for cardiac complications during implantation, there have been concerns about the use of the Micra TPS device in frail elderly patients due to the size of the insertion tool. However, previous reports have demonstrated that implantation of a leadless pacemaker in advanced age is safe and effective [10][11][12][13]. Since the number of elderly patients in need for a pacemaker increases, it is of paramount importance to gain more information on the efficacy and especially safety of Micra TPS implantation in this population.…”
Section: Introductionmentioning
confidence: 99%
“…4 Safety and efficacy of LPs was pointed out by several studies, even in older patients. 5,6 Indeed, in this case was considered the best option among pacing systems, due to old age and comorbidity of the patient, conditions that increase the risk of severe device-related complications. Furthermore, a duration of the battery was expected to be beyond the life-expectancy of the patient, due to the intermittent nature of AVB.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] They may offer new opportunities for patients with previous infections, device extraction and more generally, for fragile and older patients. [4][5][6] This case report describes a management strategy of a patient with a history of multiple previous device replacements, extractions, and malfunction of conventional transvenous systems, who underwent a successful LP implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Leadless pacemakers (LPs) have shown a high profile of safety and efficacy 1–3 . They may offer new opportunities for patients with previous infections, device extraction and more generally, for fragile and older patients 4–6 …”
Section: Introductionmentioning
confidence: 99%